2020
DOI: 10.21203/rs.2.16203/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The hospice as a learning environment: A follow-up, qualitative study with palliative care professionals and school teachers involved in a previous death education intervention

Abstract: The authors have withdrawn this preprint due to author disagreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Experiences of DeEd as primary prevention have shown that it does not produce negative effects but allows better management of related anxiety, decreases alexithymia, increases empathic understanding of others and approaches them by learning to understand their viewpoints and emotional experiences and to re-evaluate aspects of one’s life [ 13 , 19 , 20 , 21 ]. Starting from different multidisciplinary contexts, DeEd can be carried out through moments of “formal” theoretical lessons, combined with “informal” lessons that may include imaginative techniques and art therapy experiences such as photovoice, phototherapy, and psychodrama [ 13 , 18 , 19 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experiences of DeEd as primary prevention have shown that it does not produce negative effects but allows better management of related anxiety, decreases alexithymia, increases empathic understanding of others and approaches them by learning to understand their viewpoints and emotional experiences and to re-evaluate aspects of one’s life [ 13 , 19 , 20 , 21 ]. Starting from different multidisciplinary contexts, DeEd can be carried out through moments of “formal” theoretical lessons, combined with “informal” lessons that may include imaginative techniques and art therapy experiences such as photovoice, phototherapy, and psychodrama [ 13 , 18 , 19 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%